2019
DOI: 10.30919/esmm5f615
|View full text |Cite
|
Sign up to set email alerts
|

A New Machine Learning Algorithm to Optimize A Reduced Mechanism of 2-Butanone and the Comparison with Other Algorithms

Abstract: View Article Online 2-butanone (methyl ethyl ketone) has been identified as a potential alternative fuel and fuel tracer in recent studies. In this work, a reduced mechanism containing 50 species and 190 reactions for 2-butanone is developed for the first time. The raw reduced mechanism is built in three parts using decoupling methodology, a reduced CC sub-mechanism, a reduced CC sub-mechanism and a detailed H /CO/C sub-4 n 2 3 2 1 mechanism. Subsequently, the self-adaptive differential evolution algorithm of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…It can be concluded that a more accurate calculation by machine learning requires more complete data. Compared to other fields such as materials, [29,30] they have a complete database of physical properties and theoretical calculation methods. However, in the current study, the shortage of reported data is a hard problem because authors do not provide exact values of some descriptors.…”
Section: Results Of Machine Learning Algorithmsmentioning
confidence: 99%
“…It can be concluded that a more accurate calculation by machine learning requires more complete data. Compared to other fields such as materials, [29,30] they have a complete database of physical properties and theoretical calculation methods. However, in the current study, the shortage of reported data is a hard problem because authors do not provide exact values of some descriptors.…”
Section: Results Of Machine Learning Algorithmsmentioning
confidence: 99%
“…A self-adaptive differential evolution algorithm is used by Wang et al in optimizing a reduced mechanism of 2-Butanone. [110] Zhang et al came up with an overview of machine learning methods for predicting the thermal conductivity of different alloys, compounds, composites, and alloys. [111] Pilania et al combined linear least square regression with kernel ridge regression in the bandgap prediction of double perovskites.…”
Section: Machine Learningmentioning
confidence: 99%
“…However, the strong correlation between the electrons and holes at the L-point are making it challenging to accurately and efficiently predict the bandgap either with ab initio calculations or with k•p perturbations. [5][6][7][8] With the recent rapid development of artificial intelligence, many black-box and phenomenological tools have been created and accepted by researchers to predict various materials properties in an economical and efficient manner [9][10][11][12][13][14][15][16][17][18][19][20][21][22] using machine learning methodologies. [23][24][25][26][27][28] Owolabi et al [29] have used support vector (SV) regression to predict bandgaps of doped TiO 2 semiconductors and to generate the crystal lattice parameters of pseudo-cubic/cubic perovskites.…”
Section: Introductionmentioning
confidence: 99%